Implementasi Pembiayaan KPR iB Hijrah dengan Menggunakan Akad Murabahah Pada Bank Muamalat Indonesia KC Malang - Maulana, Firman Kholid; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aims of this research are: 1) To find out how the Murabahah Agreement is implemented in iB Hijrah KPR Financing at Bank Muamalat Indonesia KC Malang, 2) To find out strategies for increasing public interest in iB Hijrah KPR financing at Bank Muamalat Indonesia KC Malang. By using a descriptive qualitative method that collects data by means of interviews, the data produced is based on observations in the field. The respondents of this research were the manager and marketing team of Bank Muamalat Indonesia KC Malang, direct and indirect observation, data collection with documents related to the object under study. The research results show that Home Ownership Credit (KPR) financing at Bank Muamalat Indonesia KC Malang can be done using a buying and selling system (murabahah). Customers who need funding can go directly to the Bank Muamalat office to submit a financing application to Bank Muamalat. Then the most effective strategy according to the Bank Muamalat KC Malang team is promotion, promotion is the most effective strategy in increasing the amount of iB Hijrah KPR financing and one of them is the anniversary promo program. Keywords: Murabahah, iB Hijrah KPR Financing